A Review of the Institution of Marriage and Analysis of the Phrase "Marriages are Made in Heaven." - Pallathadka, Laxmi Kirana; Pallathadka, Harikumar; Devi, Takhelchangbam Brajeshwari (Integrated Journal for Research in Arts and Humanities, 2022)
Marriage organizations are an experienced social system, providing a system in which the overall super-building of civilization and success is built. With different individual regulations, the idea of ​​marriage has different meanings, from sacred to legally binding unions. Overall, India is still seen by the world as a country where marriage has a rational and fundamentally sacred position. In any case, the adaptation of contemporary design has changed the general idea of ​​marriage. Today, in our general public, we are changing from organized partnerships with love relationships to partnerships with same-sex marriages. You can feel it; Relationships are made in paradise. It is a notable saying. When the two meet and the marriage is over, this is recognized as the will of God. Marriage can be between similar statuses or ranks. Relationships within similar ranks mean that both children and young women have places with similar environments. A buried standing relationship means that young women and children come from different stations, some of which are lower.